(untitled) (Darya Ganj, New Delhi, 1998)
Contents of material: 1/ Book and libraries: A social overview. 2/ Research factor and libraties. 3/ Miniaturisation and technology options in retrieval. 4/ Information science HRD approaches to training. 5/ Practical classification and cataloguing. 6/ Manual of universal decimal classification.
Keywords: Libraries,Library science,Library education; Automation